eHealth Seervice in Cloud Computing Infrastructures - Koukoulis Kyriakos (2016)
Introduction, Literature Review, Cloud Computing, Cloud Computing and Classification, Classification of E-Health Cloud Computing, Cloud Computing Suitable for Healthcare Applications, Safety Reference Model EHR, Secure Integration of EHR Model, Cryptography and Access Management, Signatures and Verification, Problems with e-Health Cloud Computing, Secure e-Health Infrastucture, Error Reporting Systems, Creating a Framework for Improving Patient Safety, Organizational Measures, Recommendations and Conclusions, General Conclusions, References.